Cost-effectiveness of first-line versus second-line use of brigatinib followed by lorlatinib in patients with ALK-positive non-small cell lung cancer - Liu, Wenjie; Huo, Gengwei; Chen, Peng (Frontiers in Public Health, 2024)
Background The ALTA-1 L trial and EXP-3B arm of NCT01970865 trial found that both brigatinib and lorlatinib showed durable and robust responses in treating ALK-positive non-small cell lung cancer (NSCLC) patients. However, brigatinib and lorlatinib treatments are costly and need indefinite administration until the disease progression. Thus, it remains uncertain whether using brigatinib followed by lorlatinib before chemotherapy is cost-effective compared to reserving these two drugs until progression after chemotherapy. Methods We used a Markov model to assess clinical outcomes and healthcare costs of treating ALK-positive NSCLC individuals with brigatinib followed by lorlatinib before chemotherapy versus a strategy of reserving these drugs until progression after chemotherapy. Transition probabilities were estimated using parametric survival modeling based on multiple clinical trials. The drug acquisition costs, adverse events costs, administration costs were extracted from published studies before and publicly available data. We calculated lifetime direct healthcare costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios from the perspective of a United States payer. Results Our base-case analysis indicated that the incremental cost-effectiveness ratios of using first-line brigatinib followed by lorlatinib compared with second-line brigatinib followed by lorlatinib is -400,722.09/QALY which meant that second-line brigatinib followed by lorlatinib had less costs and better outcomes. Univariate sensitivity analysis indicated the results were most sensitive to the cost of brigatinib. Probability sensitivity analysis revealed that using brigatinib followed by lorlatinib before chemotherapy had a 0% probability of cost-effectiveness versus delaying these two drugs until progression after chemotherapy at a willingness-to-pay threshold of 150,000 per QALY. Sensitivity analyses conducted revealed the robustness of this result, as incremental cost-effectiveness ratios never exceeded the willingness-to-pay threshold. Conclusion Using brigatinib as first-line treatment followed by lorlatinib for ALK-positive NSCLC may not be cost-effective given current pricing from the perspective of a United States payer. Delaying brigatinib followed by lorlatinib until subsequent lines of treatment may be a reasonable strategy that could limit healthcare costs without affecting clinical outcomes. More mature data are needed to better estimate cost-effectiveness in this setting.